Enhancement Receiver Sensitivity Under Heavy Attenuation Effect for FSO System via Double Transmission Technique - S.A., Kwang.Thai; Abdul Rahman, Kram; S. A., Aljunid; Rosdisham, Endut; N., Ali; Che Beson, M. Rashidi (American Institute of Physics, 2024)
This paper focus on improvement of receiver sensitivity for free space optical communication. FSO communication is frequently drop performance when facing bad weather. In this research proposed new development of transmitter and receiver design in order to reduce the impact of atmospheric attenuation and increase receiver sensitivity. The analysis performance will compare with conventional amplitude shift keying (ASK) approach. Simulation result will be used to measure the performance and comparison between conventional and new proposed modulation double transmission balance receiver (DTBR) will also presented. The measurement of result will involve the effect of geometrical loss, data bit rate and distance propagation. From the result, the DTBR is increase the receiver sensitivity in term of bit error rate (BER) performance.